Judgment on Marriage With Adulterer in M.K.Bakuvi’s Interpretation of “Kashful-hagayig” and Jurisprudential Analysis of Verse 3 of Surah “an-nur” - Aghamoghlanov, Hilal (Scholarya Demo Journal of Ruby, 2021)
One of the verses in the Qur'an that contains Sharia laws is the verse 3 of Surah “an-Nur”. The author of the interpretation of “Kashful-Hagayig” Mir Mahammad Karim Bakuvi took a different approach to the interpretation and commentary of this verse, took evidence the apparent and literal meaning of the Qur'an verse, did not divide the adulterer into single and married, those who were well-known in adultery and those who were not, he did not say whether repentance was a condition for marriage, and ruled that marriage with an adulterer was haram. He also considered that marrying an adulterer was against Islam, and therefore, as a result, he allowed marrying a polytheist. Reviewing the jurisprudential analysis of the verse, it does not seem to be a proof that marriage with an adulterer is haram. The verse does not refer to Sharia law. Such approach of jurists to the verse is also reflected in their rulings on the matter. Those who consider such marriage haram have ruled that it is permissible on the condition of repentance. Scholars who attribute the verse to women who were openly engaged in prostitution in the preIslamic period considered it an evidence for permission to marry an adulterer, while those who thought that it was a clear sign of haram considered it an evidence for forbiddance to marry them. There are also different opinions on the annulment (change) of the verse's ruling. Accordingly, those who claim that it has been annulled (changed) have ruled that marriage is permissible, those who claim that it has not been annulled, but do not have Sharia law meaning, have also ruled that it is permissible, and those who claim that it has not been annulled and that it has Sharia law meaning have ruled that it is haram. Another important factor influencing Sharia ruling on this issue is that the companions (sahabah) and their followers (tabi’un) have different opinions. This difference is also reflected in the rulings of the jurists.